Relationship between body functions and referral to rehabilitation post-stroke - Eleazar Marinho de Freitas Lucena; Kátia Suely Queiroz Silva Ribeiro; Ronei Marcos de Moraes; Robson da Fonseca Neves; Geraldo Eduardo Guedes de Brito; Renata Newman Leite Cardoso dos Santos
Abstract Introduction: Stroke has a high prevalence in the world's population and a significant impact on those affected. Objective: To determine the relationship between body functions evaluated according to the International Classification of Functioning, Disability and Health (ICF) parameters and the referral of post-stroke subjects to rehabilitation services in the city of João Pessoa-PB. Methods: This study was an observational cross-sectional study involving patients diagnosed with stroke who were affected for less than 60 months and linked to the Family Health Strategy (Estratégia de Saúde da Família - ESF). The ICF stroke core sets that identify disabilities in the body function dimension were used to construct the research instrument. Access to rehabilitation was explored using a questionnaire developed from a literature review. The statistical method of logistic regression was used to identify the disabilities in body functions that were relevant to the referral of the post-stroke subject for rehabilitation. Results: The functions that were significant (p < 0.05) were functions relating to muscle tone (OR = 2.38), functions relating to voluntary movement control (OR = 2.60), emotional functions (OR = 2.22), and sexual functions (OR = 3.92). Conclusion: The findings of this study indicate that the presence of disability in these functions is associated with the referral of chronic phase post-stroke subjects to rehabilitation. Therefore, rehabilitation services should be organized to meet the specific requirements of treatment of the sequelae caused by stroke.